1988
DOI: 10.3358/shokueishi.29.7
|View full text |Cite
|
Sign up to set email alerts
|

Excretion, Distribution and Metabolic Fate of Sodium o-Phenylphenate and o-Phenylphenol in the Rat

Abstract: Excretion, organ distribution and metabolic fate of sodium o-phenylphenate (OPP-Na) and o-phenylphenol (OPP) were studied in male rats mainly with 14C-compounds. Both OPP-Na and OPP were rapidly excreted in the urine and feces following oral administration. About 85-90% of the dose appeared in the urine, but only 3-4% in the feces within 48 hr. Biliary excretion amounted to about 27% of the dose 72 hr after oral administration of OPP-Na, and was higher than that in the feces. This fact suggests that enterohepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The primary routes of OPP metabolism are shown in Scheme 1. o-Phenylphenol is metabolized enzymatically into unconjugated phenylhydroquinone (PHQ), phenylbenzoquinone (PBQ), and glucuronide and sulfate conjugates, with the urinary levels of glucuronide conjugates as well as free metabolites increasing with dose (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary routes of OPP metabolism are shown in Scheme 1. o-Phenylphenol is metabolized enzymatically into unconjugated phenylhydroquinone (PHQ), phenylbenzoquinone (PBQ), and glucuronide and sulfate conjugates, with the urinary levels of glucuronide conjugates as well as free metabolites increasing with dose (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The primary routes of OPP metabolism are shown in Scheme . o -Phenylphenol is metabolized enzymatically into unconjugated phenylhydroquinone (PHQ), phenylbenzoquinone (PBQ), and glucuronide and sulfate conjugates, with the urinary levels of glucuronide conjugates as well as free metabolites increasing with dose ( ). Due to the reactivity of quinoid compounds, it has been proposed that PBQ is responsible for the toxic effects observed in rats administered high doses of OPP and SOPP ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…Nach akuter oraler Verabreichung hoher Dosen (von bis zu 500 mg/kg KG) an OPP und OPP-Na werden praktisch 100% der verabreichten Stoffe überwiegend in Form von Schwefelsäure-oder Glucuronsäurekonjugaten in Urin (etwa 95%) und Faeces (etwa 5 %) wiedergefunden, wobei etwa 80% (OPP-Na) bzw. etwa 60 % (OPP) bereits innerhalb der ersten 12…”
Section: Allgemeiner Wirkungscharakterunclassified
“…Der Metabolismus von OPP und OPP-Na wurde überwiegend an der Ratte untersucht [7][8][9][10][11][12][13][14][15][16] und ist weitgehend aufgeklärt. Weitere Untersuchungen zum Metabolismus von OPP wurden an Hund und Katze [17][18][19][20], an der Maus [21] sowie an isolierten Hepatozyten der Ratte [22] durchgeführt.…”
Section: Pharmakokinetik Und Metabolismusunclassified
“…It is widely accepted that many carcinogens are readily converted to reactive intermediates by drug-metabolizing enzymes. The metabolites of OPP in the free form include Di-OH-BP and PBQ (8,11,12). Morimoto et al reported that DNA damage was induced in urinary bladder epithelium of male rats treated with PBQ (13).…”
Section: Introductionmentioning
confidence: 99%